Pemanfaatan Ekstrak Daun Nimba (Azadirachta indica A. Juss) untuk Pengendalian Penyakit Layu Fusarium pada Tanaman Tomat (Lycopersicum esculentum Mill.) - Juni Safitri Muljowati; Aris Mumpuni (Fakultas Biologi | Universitas Jenderal Soedirman, 2007)
The aim of this study was to find out the effect of neem leaf extract (Azadirachta indica A. Juss.) on the growth medium of tomato plant toward fusarial wilt and to determine effective concentration and time of application of the extract to control the wilt. Experiments arranged in a Completely Randomized Design (CRD) was employed for in vitro antimicrobial assay and in a Randomized Complete Block Design (RCBD) for in planta antimicrobial assay, both of which were to find out the inhibitory effect of the extract on colony growth of Fusarium oxysporum (Schlecht). f.sp. lycopersici (Sacc.) Snyd. et Hans. (Fol). The results indicated that neem leaf extract concentration of 5% applied at 7 DAP (Day After Planting) was the most effective treatment in inhibiting disease intensity of fusarial wilt on tomato plant showing inhibitory effect of up to 89.32%.